Supporting Factors on Healthy Lifestyle at Elementary School - Endah Retnani Wismaningsih; Tegar Wahyu Yosuanto; Serviana Devi; Vivien Dwi Purnamasari; Reny Nugraheni; Ratna Frenty Nurkhalim; Dianti Ias Oktaviasari (International Journal of Health Literacy and Science, 2023)
Washing hands with soap with flowing water and prefer healthy snack are linked healthy lifestyle especially for elementary students. Because one of important time for washing hands with soap are before and after eating or snacking. So, both healthy lifestyles are important in student’s health status, but many students do not practice it. This research aims to identify supporting factor on healthy lifestyle that are washing hands with soap and healthy snacking at elementary school. This research used qualitative methods with in-depth interviews, observation, and documentation to collect the data from main informant that is students and key informants that are school principal, teacher, canteen keeper. The result of this research were facilities (hand wash facilities and healthy canteen), implemented health promotion in the form of pasted media, social support, and student’s personal skill to practice it were the supporting factors on healthy lifestyle that are washing hands with soap and healthy snacking at elementary school.